Türk Parlamento tarihinde iki kanatlı meclisler - Bilgü, Hamza (My University, 2018)
Osmanlı Devleti bürokrasisinde 19. yüzyılda başlayan anayasal hareketler neticesinde 1876 yılında Türk siyasi tarihinin ilk anayasası Kanun-i Esasi ilan edilmiştir. Kanun-i Esasi'nin ilanıyla birlikte Osmanlı Devleti, Meşrutiyet rejimiyle idare edilmeye başlanmıştır. Meşrutiyet idaresinin en önemli kurumu Meclis-i Umumi olarak adlandırılan parlamentodur. Meclis-i Umumi, Meclis-i Âyan ve Meclis-i Mebusan olmak üzere iki kanatlı yapı arz etmektedir. Meclis-i Âyan atanmışlar, Meclis-i Mebusan ise seçilmişler meclisi olacak şekilde kurgulanmıştır. Padişah II. Abdülhamit'in tatil kararıyla Meclis-i Mebusan'ın çalışmaları sekteye uğramış, Meclis, 1908 yılında tekrar faaliyete geçmiş ve 1920 yılına dek çalışmalarını sürdürmüştür.I. Dünya Savaşıyla birlikte Osmanlı Devleti dağılma sürecine girmiştir. 1920 yılında Mustafa Kemal önderliğinde kurulan Türkiye Büyük Millet Meclisi, Osmanlı'nın mirası üzerinde inşa edilecek olan Türkiye Cumhuriyeti'nin habercisi olmuştur. 1923 yılında kurulan yeni devletin yönetim şeklinin Cumhuriyet olmasına karar verilmiştir. 1960 yılına dek Türkiye Büyük Millet Meclisi, faaliyetlerini tek meclis şeklinde sürdürmüştür.1960 yılında gerçekleşen darbenin akabinde, 1961 yılında yeni bir anayasa yapılmıştır. Bu anayasada Türkiye Büyük Millet Meclisi'nin, Cumhuriyet Senatosu ve Millet Meclisi olmak üzere iki kanatlı yapı arz etmesine hükmedilmiştir. Cumhuriyet Senatosu, doğal üyeleri ve Cumhurbaşkanı tarafından atanan 15 üyesi dışında seçilmişlerden oluşacaktır. Millet Meclisi ise tamamiyle seçilmişlerden ibaret bir meclistir. Cumhuriyet tarihinin bu ilk ve tek iki kanatlı meclisi, 1980 yılına dek faaliyet göstermiştir. Bu tezde öncelikle Osmanlı Devleti'nde anayasal-parlamenter hareketler, demokratikleşme çabası ve Osmanlı modernleşmesi ele alınmıştır. Ardından ilk anayasa Kanun-i Esasi'nin içeriği incelenmiş, öngördüğü yasama meclisinin yapısı aktarılmıştır. Daha sonra Meclis-i Umumi, genel hatlarıyla incelenmiştir. Meclis-i Mebusan ve Meclis-i Âyan, seçimleri, yapıları ve faaliyetleri bağlamında detaylı olarak aktarılmıştır. Akabinde 1961 Anayasası'nın nasıl bir yasama meclisi öngördüğü belirlenmiştir. 1961 yılında 1980 yılına dek faaliyet gösteren Türkiye Büyük Millet Meclisi'nin her iki kanadı mercek altına alınmıştır. Cumhuriyet Senatosu ve Millet Meclisi, seçimi, yapısı ve faaliyetleri bakımından incelenmiştir.Tezde son olarak Kanun-i Esasi ve 1961 Anayasası'nın yasama bölümleri ile iki kanatlı Meclis-i Umumi ile iki kanatlı Türkiye Büyük Millet Meclisi'nin yapıları, faaliyetleri karşılaştırılmıştır. Böylelikle parlamento tarihimizin iki farklı iki kanatlı meclis tecrübesinin ne şekilde yaşandığı ortaya konmuş, 1876 yılından 1980 yılına dek Türk anayasa hareketleri ve demokrasi macerasının seyrini anlayabilmek için bir izlek oluşturulması amaçlanmıştır.

The Basic Law (Kanun-i Esasi) was declared in 1876 as the consequence of constitution-oriented movements started in 19th century in the Ottoman Empire, which led the Empire to shift its system from monarchy to constitutional monarchy. The most important institution of this constitutional monarchy is General Assembly (Meclis-i Umumi) that has a double-wing structure consisting of Notables Assembly (Meclis-i Ayan) and Chamber of Deputies (Meclis-i Mebusan). The former one included the assigned, while the latter one had the elected. Upon the leisure resolution of Abdulhamid The Second, Chamber of Deputies halted working and then came into effect again in 1908, thus worked until 1920. The dissolution of Ottoman Empire began following the First World War. And Grand National Assembly of Turkey, founded under the leadership of Mustafa Kemal Atatürk in 1920, was the precursor of Turkish Republic to be found based on the legacy of Ottoman Empire. Soon after, it was decided that the new state, founded in 1923, would be governed with a Republican regime. Until 1960, Grand National Assembly of Turkey carried on its activities under the roof of just one assembly. Right after the coup d’etat in 1960, a new constitution was established in 1961. And with this constitution, Grand National Assembly of Turkey was concluded to have a double-wing structure including Republican Senate and National Assembly (Parliament). The Senate would consist of elected representatives other than its ordinary members and 15 members assigned by the President, while Parliament consisted only of the elected ones. This first and only double-wing assembly of Republican history was in service until 1980. Constitutional and parliamentary movements, democratization attempts and modernization in the Ottoman Empire have been tackled throughout this thesis. And then the content of Basic Law, the very first constitution of Ottoman Empire, has been examined and analyzed, while the structure of legislative assembly projected by it has been conveyed. Afterwards, The General Assembly (Meclis-i Umumi) has been reviewed with broad strokes. Chamber of Deputies and Notables Assembly have been remarked in detail with their way of elections, structures and activities, which is followed by a specification about what kind of a legislative assembly was projected by 1961 Constitution Act. Having worked from 1961 to 1980, both wings of Grand National Assembly of Turkey have been scrutinized. Election method, structure and activities of both Republican Senate and National Assembly (Parliament) have also been examined. Lastly, legislative parts of Basic Law and 1961 Constitution Act and structures and activities of double-wing General Assembly and double-wing Grand National Assembly of Turkey have been compared. Therefore, how two different double-wing assemblies were experienced have been revealed and a path to understand Turkish constitutional movements from 1876 to 1980 and Turkey’s democracy journey has been aimed to create.
Keywords: 1961 Anayasası; 1961 Constitution Act; Anayasa; Anayasa tarihi; Basic Law; Chamber of Deputies; Constitutional history; Constitutional Monarchy; Cumhuriyet Senatosu; Çift Meclis; Double-Assembly System; Double-Wing Assembly; Grand National Assembly of Turkey; History; İki Kanatlı Meclis; Kanun-i Esasi; Legislative bodies; Meclis-i Âyan; Meclis-i Mebusan; Meşrutiyet; Millet Meclisi Constitution Act; National Assembly; Notables Assembly; Parlamento; Parliament; Republican Senate; Tarih; Turkey; Turkey. Büyük Millet Meclisi; Türkiye; Türkiye Büyük Millet Meclisi; Türkiye. Büyük Millt Meclisi; Yasama organları